How to assess diabetes distress: comparison of the Problem Areas in Diabetes Scale (PAID) and the Diabetes Distress Scale (DDS). Issue 6 (8th September 2015) - Schmitt, A.; Reimer, A.; Kulzer, B.; Haak, T.; Ehrmann, D.; Hermanns, N.
Abstract: Aims: To compare the properties of the two most commonly used assessment tools for diabetes distress, the Problem Areas in Diabetes Scale (PAID) and the Diabetes Distress Scale (DDS), in order to discriminate their psychometric capabilities and functions. Methods: Six hundred and twenty‐eight people with diabetes (67% Type 1, 33% Type 2) were cross‐sectionally assessed with the PAID, the DDS and further self‐report scales regarding coping, quality of life, depressive symptoms and self‐care, and medical data were gained. We analysed the PAID and DDS for areas of contentual/psychometric divergence in assessing diabetes distress and compared their associations with criteria of interest. Results: Content analysis : The PAID covers a greater variety of emotional concerns and shows a stronger focus on food‐related problems and complications. The DDS is more reflective of physician‐related distress and problems concerning diabetes self‐management. Psychometric analysis : Exploratory factor analyses revealed four‐factor structures of both scales, explaining 60% (PAID) and 67% (DDS) of variance. Confirmatory factor analyses confirmed that single‐factor and four‐factor models fit the data. Total scales proved high and subscales mostly satisfactory reliability. Associations with criteria of interest : The PAID was significantly more strongly associated with dysfunctional coping styles, quality of life and depressive symptoms. The DDS showed significantly stronger associations with diabetes self‐care and metabolic outcomes. Conclusion: Our results support both PAID and DDS as good self‐report measures of diabetes distress. The observed contentual/psychometric differences suggest that a justified choice with regard to the intended clinical or scientific purpose can improve the acquisition of the required data. What's new?: This is the first study to carry out direct psychometric comparisons of the two most commonly used measures of diabetes distress. The Problem Areas in Diabetes Scale (PAID) covers a greater variety of emotional concerns, whereas the Diabetes Distress Scale (DDS) is more reflective of distress concerning diabetes self‐management. The DDS has a more precise and cross‐culturally consistent factor structure than the PAID. Higher PAID scores are more strongly associated with dysfunctional coping, quality of life and depression. Higher DDS scores are more strongly associated with reduced self‐care and metabolic control.